Intergenerational coresidence living arrangements of young adults with their parents in Taiwan: The role of filial Piety - Yen-Jong Chen; Rodney H. Matsuoka; Hsi-Chuan Wang (Journal of Urban Management, 2022)
Young adults throughout the world today, including those in Taiwan, are permanently leaving their parents' homes at a much later age compared with their parents' generation, a situation labeled as the failure-to-launch or boomerang generation. What role do filial piety beliefs play in East Asian especially in Chinese societies concerning intergenerational coresidence? Most studies on filial piety have examined older adult children and post-retirement parents, and have not simultaneously considered the viewpoints of both generations, which was investigated by using a two-level nested logit model. A sample of 657 families was selected from the Panel Study of Family Dynamics (PSFD), conducted in Taiwan from 1999 to 2007. The young adult factors of having fewer economic resources and being unmarried were more important than their parents' having greater economic resources and other demographic characteristics, and the filial piety beliefs of young adults were less significant, but still associated with intergenerational coresidence.
Keywords: 710; Young adults; Intergenerational coresidence; Chinese filial piety norms; Living arrangement; Discrete choice